The Effect of Firm Internal and External Characteristics on Risk Reporting Practices among Malaysian Listed Firms - Ali, Mazurina Mohd; Bakar, Ruzzana Abu; Ghani, Erlane K. (Indonesian Journal of Sustainability Accounting and Management, 2018)
: This study examines the effect of firm internal and external characteristics on risk reporting practices among the Malaysian public listed firms. Specifically, this study focuses on three internal characteristics namely, duality of board leadership, the presence of stand-alone risk management committee, and length of CEO tenure and external characteristics namely, competition, debt governance and auditor quality on the risk reporting practices among the Malaysian public listed firms. Using, content analysis on 200 top public listed firms in Bursa Malaysia, this study shows that one of the external characteristics namely, debt governance significantly influence risk disclosure among the Malaysian public listed firms. This study however, shows that none of the internal characteristics influence risk disclosure among the Malaysian public listed firms. The findings of this study provide further understanding on the factors influencing risk disclosure of Malaysian public listed firms.